2016
DOI: 10.1093/ajh/hpw150
|View full text |Cite
|
Sign up to set email alerts
|

Central Haemodynamics and Prediction of Cardiovascular Events in Patients With Erectile Dysfunction

Abstract: Our results show for the first time that higher central pressures and AIx are associated with increased risk for a MACE in ED patients without known CV disease. Considering the adverse prognostic role of central hemodynamics on outcomes, the present findings may explain part of the increased CV risk associated with ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Two recent studies, one of them a metaanalysis, concluded that ED is a predictor of future cardiovascular events, independently of other associated risk factors. 36,37 In this study, performed in patients with ED and subsequently diagnosed with periodontitis, we confirmed and quantified the highest occurrence of MACEs. Seven patients with both diagnoses, suffered 10 MACEs events (three patients, two events), compared to three patients with a single event each, in the other groups (no patient with two events).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Two recent studies, one of them a metaanalysis, concluded that ED is a predictor of future cardiovascular events, independently of other associated risk factors. 36,37 In this study, performed in patients with ED and subsequently diagnosed with periodontitis, we confirmed and quantified the highest occurrence of MACEs. Seven patients with both diagnoses, suffered 10 MACEs events (three patients, two events), compared to three patients with a single event each, in the other groups (no patient with two events).…”
Section: Discussionsupporting
confidence: 64%
“…These data support the hypothesis of considering ED as an early diagnosis manifestation to predict a future MACEs. Two recent studies, one of them a meta‐analysis, concluded that ED is a predictor of future cardiovascular events, independently of other associated risk factors 36,37 …”
Section: Discussionmentioning
confidence: 99%
“…Several pathological factors that affect the blood vessels, such as atherosclerosis, endothelial dysfunction, and inflammation, can result in arteriogenic ED . In most patients with arteriogenic ED, the changes in morphology and structure caused by penile atherosclerosis reduce the filling of the cavernous body of the penis, resulting in an inability to meet the demand for blood volume during erections . Moreover, vascular endothelial dysfunction that occurs in atherosclerosis plays a pivotal role in arterial erectile dysfunction …”
Section: Introductionmentioning
confidence: 99%
“…In one study, it was shown that the increase in aortic vascular stiffness is significantly associated with increased severe cardiac side effects in ED patients without known cardiac disease. This study reports that PWV measurements can be used to determine cardiac risk in patients with ED (Vlachopoulos et al, ).…”
Section: Discussionmentioning
confidence: 99%